2001
DOI: 10.1046/j.1471-4159.2001.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of glial glutamate transporters in the parietal cortex and hippocampus of the EL mouse

Abstract: There is extensive experimental evidence indicating a crucial role for glutamate in epileptogenesis and epileptic activity. The glial glutamate transporters GLT1 and GLAST are proposed to account for the majority of extracellular glutamate reuptake. In the present study, polyclonal antibodies speci®c to GLT1 and GLAST were generated and characterized, revealing distribution patterns for the two transporters con®rming those previously reported. In situ hybridization and immunoblotting were then used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Some works have shown that decreased glutamate transporter activity is related to seizures (Meldrum, 1994;Ingram et al, 2001;Maragakis and Rothstein, 2001). In our study, pretreatment with MK-801, DNQX or adenosine significantly prevented the decrease of glutamate uptake when seizures were avoided.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Some works have shown that decreased glutamate transporter activity is related to seizures (Meldrum, 1994;Ingram et al, 2001;Maragakis and Rothstein, 2001). In our study, pretreatment with MK-801, DNQX or adenosine significantly prevented the decrease of glutamate uptake when seizures were avoided.…”
Section: Discussionsupporting
confidence: 63%
“…It has been suggested that impaired astrocytic glutamate uptake may be involved in epileptogenesis. Studies with epileptic mice and rats presenting chronic seizures induced by kainic acid showed a decrease in astrocytic glutamate transporters GLT-1 and GLAST (Ingram et al, 2001;Ueda et al, 2001). Moreover, quinolinic acidinduced seizures decrease brain glutamate uptake in young and adult rats (Oliveira et al, 2004;Vinade et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…102 In a seizuresusceptible mouse strain, GLT1 mRNA and protein were downregulated in the parietal cortex, whereas in the hippocampus there was a decrease in mRNA expression without a corresponding decrease in the protein level. 103 This observation was corroborated in another study of genetically epilepsy-prone animals showing decreased GLT1 RNA expression in the cortex, striatum, CA1 and the inferior colliculus, without a corresponding change in protein levels. 104 The changes in RNA expression that are not reflected at the protein level suggest that post-transcriptional regulation of GLT1 may differ between seizuresusceptible and control animals.…”
Section: Epilepsymentioning
confidence: 56%
“…In the EL (epileptic) mouse the hippocampus is important for the generation of behavioural seizures. However, there is no neuronal injury or loss in this model but an increase in expression of astrocytes around the age when seizures appear (Drage et al, 2002), and these astrocytes have reduced glutamate transporters, suggesting a primary role for astrocytes, perhaps through defective glutamate clearance at the seizure focus (Ingram et al, 2001). More direct evidence is found mice in which there is astrocyte-specific inactivation of the Tsc1 gene (Tsc1 cKO mice).…”
Section: The Chronic Astrogliopathology: Epilepsymentioning
confidence: 93%